Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c6cp08114b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of core–shell structures driven by low doping limit of Ti in LiCoO2: first-principles thermodynamic and experimental investigation

Abstract: Introducing additives is a general method of performance improvement in materials engineering, but details regarding whether the additive is doped in the host crystal or present as a secondary phase are usually examined from experimental experience, with a systematic theoretical prediction lacking, which sometimes causes controversy on the role of additives. In this study, the dopability of Ti in crystalline LiCoO (LCO) is investigated by a first-principles simulation method, and the doping limit is quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…[ 69a ] Recent results indicate that only small amount of Ti (<0.15%) can be doped into LiCoO 2 lattice and most of them enrich on the surface/interface of LiCoO 2 . [ 26,77 ] Al is one of the most attractive dopants due to strong AlO bond, similar valence and ionic radius with Co in LiCoO 2 . Ceder et al first predicted theoretically and demonstrated experimentally that the Al doping is able to increase the open‐circuit voltage and working voltage of LiCoO 2 .…”
Section: Modificationsmentioning
confidence: 99%
“…[ 69a ] Recent results indicate that only small amount of Ti (<0.15%) can be doped into LiCoO 2 lattice and most of them enrich on the surface/interface of LiCoO 2 . [ 26,77 ] Al is one of the most attractive dopants due to strong AlO bond, similar valence and ionic radius with Co in LiCoO 2 . Ceder et al first predicted theoretically and demonstrated experimentally that the Al doping is able to increase the open‐circuit voltage and working voltage of LiCoO 2 .…”
Section: Modificationsmentioning
confidence: 99%
“…Because structure disintegration usually commences around the crystal surface 17 , 18 , and considering the specific capacity, an effective surface-enrichment gradient doping is required for this cathode. Theoretical calculations revealed that the doping efficiency is generally low because of easily formed dopant-containing electrochemical inert compounds on the particle surface 19 , 20 . Because of the sensitivity of the Ni-rich oxide precursor to moisture and air, and abundant Li source (i.e., Li 2 CO 3 , LiOH) 21 , 22 , the traditional multistep coating and doping approach is undesirable for industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reports, an entire crystal was considered as the combination of unit supercells containing each type of defect. The probability of each defect type, or the proportion of each supercell unit in the entire crystal, was calculated by considering the mixing entropy of the units, which demonstrated that the proportion of each unit was determined by the Boltzmann factor. Therefore, in this study, the macroscale LNCM crystal is considered as an ensemble system comprising a combination of supercell units that may be Zr‐doped or undoped, and the ratio between the doped and undoped units is determined by the Boltzmann factors.…”
Section: Resultsmentioning
confidence: 99%